The treatment of venous thromboembolism with low-molecular-weight heparins - Bochenek, Tomasz; Nizankowski, Rafal (Thrombosis and Haemostasis, 2012)
The currently recommended method of venous thromboembolism (VTE) treatment is the application of vitamin K antagonists (VKA) in most patients, and low-molecular-weight heparins (LMWH) in selected groups. The VKA dose adjustment is difficult which might well render the treatment ineffective. The study aimed to compare LMWH with VKA in treating VTE in terms of efficacy and safety. A systematic review of literature and the meta-analysis of the treatment results were performed. The main differences between LMWH and VKA in terms of their respective effectiveness in treating VTE consist in appreciably more advantageous effects of LMWH in preventing deep venous thrombosis (DVT). The key difference in terms of respective safety is the greater effectiveness of LMWH in preventing minor bleedings. The advantage of LMWH in cancer patients consists predominantly in a significantly better protection against DVT episodes, whereas the advantage of LMWH in non-cancer patients is mainly owed to better protection against minor bleedings. In none of the analysed outcomes of VTE treatment, the application of VKA proved to hold any advantage over LMWH. Although, arguably, there might well be sufficient medical grounds to propose more widespread use of LMWH, it still remains a debatable issue whether the currently used therapeutic standard should also be modified accordingly. Apart from the actual findings of the present meta-analysis, pertinent economic considerations must also be addressed.
Keywords: Venous thromboembolism; low-molecular-weight heparin/LMWH; vitamin K antagonist/VKA; systematic review; meta-analysis